TYPES OF RISKS WITHIN PROJECTS - Irina Andreea PEGULESCU (Management & Marketing)
The realization of a project requires the application of stages, which are often prone to the appearance of risks. They can affect, negatively or positively, the evolution of a project, from all points of view. A good identification and framing of risks can lead to their effective management, throughout the life of a project, in order to implement an effective project. Through the present research, we consider the global framing of risks, to support their effective management, for the benefit of projects.